Do Constitutional Preferences Affect Citizens' Representational Choices? Evidence from the Devolved UK. Issue 1 (1st August 2021) - Convery, Alan; Parker, David C W; Haines, Pavielle E; Johnson, Sheridan; Schmidt, Rachel
Abstract: The creation of the Scottish Parliament provided Scottish citizens with an additional layer of politicians to represent them. But to whom do constituents turn when seeking help with a problem—councillors, MSPs or MPs? We assess how partisanship, national identity and shared competences affect public perceptions of the governing responsibilities of the UK Parliament, Scottish Parliament and local councils. We find that an individual's national identity considerably affects perceptions of the political powers delegated to Scottish political institutions. We conclude by considering the implications for efforts to further devolve powers to the devolved legislatures in the UK.